Consumer Sensory Evaluation of the Impact of Bone-In Versus Boneless Cuts on Beef Palatability - K. J. Farmer; E. S. Beyer; S. G. Davis; K. M. Harr; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to determine palatability traits of beef cuts of differing bone status and quality grade. Study Description:Paired (n = 12 pairs; 24 total/cut/grade) boneless and bone-in ribeye rolls, and short loins were procured. Short loins were fabricated into boneless strip loins with corresponding bone-in tenderloins or bone-in strip loins with boneless tenderloins. Post aging, subprimal cuts were fabricated into steaks that were randomly selected for further analysis. Consumer sensory panelists (n = 144) were recruited from Manhattan, KS, and the surrounding area and paid for their participation in the study. Panels were conducted in a lecture-style classroom at Kansas State University. Results:In totality, bone status had a minimal impact on palatability traits. Bone state had no impact (P>0.05) on consumer juiciness and overall liking for tenderloins and ribeyes, but in the strip loin, bone-in steaks were rated juicier (P<0.05) and higher (P<0.05) for overall liking when compared to boneless steaks. Moreover, bone state had no impact (P>0.05) on consumer tenderness and flavor ratings for any of the three cuts. Bone state had no impact (P>0.05) on the percentage of consumers that rated juiciness as acceptable for tenderloins and ribeyes, but in strip loins, bone-in steaks had a higher (P<0.05) percentage of acceptable consumer responses than boneless cuts. The percentage of acceptable samples for tenderness and overall acceptability were not (P>0.05) impacted by bone state in tenderloins and strip loins; however, in ribeyes, the percentage of acceptable consumer ratings was higher (P<0.05) for bone-in cuts for both traits. Bone state also did not (P>0.05) impact premium, better than everyday, and everyday quality perceptions among ribeyes; but the percentage of consumers rating ribeye samples unsatisfactory was higher (P<0.05) for boneless ribeye steaks. The Bottom Line:A similar overall eating experience could be derived from a boneless or bone-in steak from the same cut and quality grade.
Keywords: bone-in; boneless; palatability